Змішана мотивація англійської теріологічної номенклатури - Рибалка, Н. С.; Rybalka, N. S. (Волинський національний університет імені Лесі Українки, 2012)
У статті висвітлено особливості змішаного типу мотивації англійських номенклатурних найменувань ссавців. Виокремлено пропозиційно-модусний і пропозиційно-асоціативний різновиди змішаної мотивації теріологічних номенів. The article focuses on cognitive-onomasiological analysis of the mixed type of motivation applied to English nomenclatorial (common) name of mammals. The author distinguishes between propositional-axiological and propositional-associative subtypes based on the status of the motivators involved.
Mixed-type Motivation in English Nomenclatorial (Common) Names of Mammals
Keywords: номенклатурні найменування ссавців; nomenclatorial (common) names of mammals; змішана мотивація; mixed type of motivation; пропозиція; proposition